SOME FUNCTIONS OF ELLIPSIS IN RELIGIOUS TEXTS - Al-duleimi, Abbas Deygan Darweesh (European Scientific Journal, ESJ, 2013)
Ellipsis is the non-expression of sentence elements whose meaning can be retrieved by the addressee. In grammatical analysis ellipsis is a term used for a sentence, where for reasons of economy, emphasis or style a part of the structure has been omitted. Using ellipsis can restrict possible readings, express otherwise ineffable meanings, clarify discourse functions and establish rapport between the addresser and the addressee.